Effect of NaBr, KCl, KBr, and MgCl2 on viscosities of aqueous glycine and L-alanine solutions at 298.15 K - Badarayani, Rohini; Satpute, D. B.; Kumar, Anil (Journal of Chemical and Engineering Data, 2005)
Viscosities, η, of glycine and L-alanine are measured in aqueous solutions of NaBr, KCl, KBr, and MgCl2 up to high concentrations at 298.15 K. This study suggests that 1:1 electrolytes enhance the structure making ability of the amino acids whereas MgCl2 does not. The viscosities of the above solutions are correlated using a simple model with two interaction parameters.

Correlations of thermodynamic properties of aqueous amino acid-electrolyte mixtures - Saritha, C.; Satpute, Dilip B.; Badarayani, Rohini; Kumar, Anil (Journal of Solution Chemistry, 2009)
Suitable equations have been proposed to correlate thermodynamic properties, like mean ion activity coefficients, volumes and compressibilities, of amino acids in electrolyte solutions. An amino acid-electrolyte-water interaction parameter is extracted from the regression of the amino acid property values in aqueous electrolyte solution that is then transferred to an expression to correlate the properties of the electrolyte in mixtures. The single interaction parameter can successfully correlate the published data on mean ion activity coefficients, apparent molar volumes and compressibilities of amino acids as well as of electrolytes in their aqueous mixtures. The equations are tested against the large number of experimental data sets available in the literature.
Keywords: Amino acids; Electrolytes; Pitzer equation; Thermodynamic properties